Using Simple Molecular Model to Enhance Students’ Understanding on Molecular Geometry Based on VSEPR Theory - Erlina Erlina; Eny Enawaty; Rahmat Rasmawan (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Numerous studies had reported that students in all level found that study chemistry is difficult. The main cause of the difficulty is the inability of students to visualize the atom or molecules. This study aims to enhance students’ understanding by using   the simple molecular model as the learning resources to help students visualize the shape of the molecules. To achieve the aim, this study employs one-group pre-test post-test design. A conceptual test was used as pre-test and post-test to measure students’ understanding before and after learning with the simple molecular model. Fifty-four first-year cohort students of Chemistry Education Study Program of Department of Mathematics and Science Education of Faculty of Teacher Training and Education, Tanjungpura University were involved in this study. Students’ pre-test and post-test scores were analysed using a paired sample t-test with SPSS. Based on data analysis, a statistically significant improvement in scores (p value = 0.001) was found, which indicates that the Simple Molecular Model could enhance students’ understanding on Molecular Geometry.